Therapeutic Management of Breast Cancer Related Upper Limb Lymphedema - Andrea GROSU-BULARDA; Flavia Francesca LITA; Adriana SERBAN; Florin Vlad HODEA; Alexandru STOIAN; Ioan LASCAR; Razvan Nicolae TEODOREANU (Modern Medicine)
Lymphedema represents a chronic condition with impaired lymphatic transport, having primary and secondary etiologies. The most common type of secondary lymphedema in western countries is represented by breast cancer related upper limb lymphedema. This condition, once installed, determines limb structure changes, progressive functional impairment, specific complications, consequently impacting the quality of patient’s life. An accurate diagnosis is mandatory, using both clinical and imagistic methods with clear definition disease extent as per standardized staging systems, in order to further provide an adequate therapeutic strategy. The main therapeutic goal in patients with lymphedema is represented by limb volume reduction with subsequent symptoms relief, improving quality of life and avoiding complications such as recurrent infections. Through this paper, we aim to present a comprehensive overview of current therapeutic options of breast cancer upper limb related lymphedema. Therapeutic approach comprises of non-surgical (conservative) therapy, which is mandatory as initial therapy and surgical procedures for selected cases. Most patients with lymphedema benefit from conservative treatment alone. In non-responsive cases, in patients with progressive disease, in late stage complicated lymphedema, and also recently added as prophylactic strategy, surgical treatment, trough recent developed techniques, offer very good results in long-term control of disease. Surgical options are classified firstly in physiologic procedures that aim to create new lymphatic channels, promote physiologic drainage of the lymph and should be considered early in the course of the disease, and secondly ablative procedures that reduce through liposuction or various excision techniques the volume of the affected limb. Both types of techniques can be combined to ensure the best functional outcome of the patient.